PEMANFAATAN POTENSI TANAMAN HIAS SEBAGAI UPAYA MENINGKATKAN MOTIVASI GENERASI MUDA UNTUK BERWIRAUSAHA BERBASIS GREEN BUSINESS DI KOTA MALANG - Pradana, Bayu Ilham; Triananda, Evi Angelina (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2024)
Ornamental plants, as the potential of Malang City, give rise to business opportunities in the field of environmental conservation. The involvement of the younger generation in business is indispensable to encourage regional economic growth. This activity aims to increase the motivation of the younger generation in green business-based entrepreneurship. The activity took place at Semi Abadi, a prominent center for ornamental plant businesses in Batu City. This event was attended by 30 members from the Youth Organization of Mojolangu sub-district, Malang City. Two methods were used in this activity, seminar and practice. The initial activity session consisted of a seminar on ornamental plant entrepreneurship held at the Semi Abadi kiosk. This was followed by the second session, which involved practical exercises in the cultivation garden. The completion of the evaluation sheet was conducted after the activity in order to assess alterations in motivation pre and post activity. The assessment of motivation involves the application of indicators, including the need for achievement, need for power, and need for affiliation. The data analyzed using the paired T-Test showed a significant increase in motivation in green business-based entrepreneurship after participating in activities when compared to before the activity on all aspects of motivation, the need for power and affiliation has increased higher than the need for achievement. Through Confirmatory Factor Analysis (CFA), the results affirm the questionnaire instrument's fit to measure motivation. The Youth Organization holds the expectation that this activity can be consistently conducted with the aid of business consulting and marketing.